Perancangan Sistem Smart Program Lembaga Motivasi Nurul Jadid Berbasis Web - M. Syafiih (Yayasan Literasi Sains Indonesia, 2022)
The Smart Program of Nurul Jadid Motivation Institute (LMNJ) is a program collection owned by two divisions, such as counseling and hypnotherapy division and the motivation and literacy division. The system that takes place in this smart program is still manual, they are students and the public society who want to consult related to psychology or literacy classes, by visiting the office room. So does the LMNJ who will promote should have society gathering intensively. This results in less than optimal management and services related to institutional activities, so a special media is needed in the form of a website to provide easily accessible online services and information. From these problems, the purpose of this research is to optimize the management and services as well as the delivery of information related to smart programs. The method used is the waterfall method, which is an effort to process information systems systematically. This smart program information system uses codeigniter. Codeigniter here is a web framework for PHP in implementing the Model View Controller (MVC) design pattern. The result of this test is to produce a web-based smart program information system application shows a percentage in 88.4% with the category is acceptable to use.